The Effects of Generative AI-based Gratitude Journaling on Adolescents’ Life Satisfaction, School Satisfaction, Self-esteem, and Anger - Chae-hee Lee; Su-Keun Yu; Juyeol Ryu; Na Young Shin (Jounral of Educational Therapist, 2026)
This study investigated the effects of generative AI-based school-life gratitude journaling on life satisfaction, school-life satisfaction, self-esteem, and anger among middle school students. Participants in the gratitude journaling group (N = 23) recorded at least three things they were grateful for regarding their school life using a generative AI application every weekday afternoon for four weeks. The wait-list control group (N = 26) received no intervention during the study period. All participants completed the Satisfaction with Life Scale, the Multidimensional School Life Satisfaction Scale, the State-Trait Anger Expression Inventory, the Rosenberg Self-Esteem Scale at pretest and posttest. Significant interactions between time and group were found for friend satisfaction, school satisfaction, and trait anger. The gratitude journaling group showed significant increases in friend satisfaction and school satisfaction and a significant decrease in trait anger following the intervention. These findings suggest that generative AI-based school-life gratitude journaling may be an effective intervention for enhancing school satisfaction and reducing trait anger among adolescents.